Correction: Sustainable visions: Unsupervised machine learning insights on global development goals. - Alberto García-Rodríguez; Matias Núñez; Miguel Robles Pérez; Tzipe Govezensky; Rafael A Barrio; Carlos Gershenson; Kimmo K Kaski; Julia Tagüeña (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0317412.].